2019
DOI: 10.3390/buildings9090190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Balcony Thermal Breaks on Building Thermal and Energy Performance: Field Experiments and Energy Simulations in Chicago, IL

Abstract: A common envelope performance problem in buildings is thermal bridging through balcony slab connections, which can be improved with the use of commercially available thermal break products. Several prior studies have used simulation-based and/or hot box test apparatus approaches to quantify the likely effect of balcony thermal breaks on effective thermal resistance of building enclosures. However, in-situ measurements of thermal performance in real buildings remain limited to date. This study uses a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The impact on the overall U-value of the building envelopes can be improved from 9-18% and the space heating energy consumption may be reduced from 5-13%. The results of research by Susorow et al [26] showed a similar level of improvement in the effective thermal resistance of the curtain wall cladding assembly in a multi-family building in Chicago (by approximately 14%). However, the predicted effect of the use of thermal breaks on the annual energy consumption was significantly lower than in [25].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The impact on the overall U-value of the building envelopes can be improved from 9-18% and the space heating energy consumption may be reduced from 5-13%. The results of research by Susorow et al [26] showed a similar level of improvement in the effective thermal resistance of the curtain wall cladding assembly in a multi-family building in Chicago (by approximately 14%). However, the predicted effect of the use of thermal breaks on the annual energy consumption was significantly lower than in [25].…”
Section: Introductionmentioning
confidence: 81%
“…However, the predicted effect of the use of thermal breaks on the annual energy consumption was significantly lower than in [25]. In several more generic building designs with simpler geometries, it was less than 2% [26]. The authors suggested the need to consider the use of thermal break products in combination with other energy efficiency strategies to achieve high performance enclosures.…”
Section: Introductionmentioning
confidence: 99%
“…These con-struction solutions can reduce the linear thermal transmittance of thermal bridges by more than 60% [38] and decrease heating consumption by 5% to 13% and cooling consumption by 1% [39]. However, other research limits the impact of thermal break disruptions in balconies on the overall thermal and energy performance of the building, demonstrating that their effect on annual energy consumption is relatively small [40].…”
Section: Of 26mentioning
confidence: 99%
“…A fi eld study [28] evaluated the infl uence of thermal break in the balcony construction on the thermal performance and energy saving of high-rise multi-unit residential buildings located in Chicago, IL, USA. The study was done by installing thermocouples on both the slab board of a thermally broken balcony and the conventional balcony slab (non-thermally broken balcony) to measure the temperature gradient.…”
Section: Sun-shade Elementmentioning
confidence: 99%